The cultural turn : scene-setting essays on contemporary cultural theory - Chaney, David C. (Routledge, 1994)
This book explains the "turn to culture" and the lessons to be drawn from this movement. The author also provides an elegant and informative guide to the importance of culture in the postmodern world. A key work in understanding culture.